Adsorptive Eradication of Cadmium(II) from Water Using Biocomposites of Polyaniline with Madhuca longifolia and Eugenia jambolana Leaves Powder - Kanwal, Farah; Rehman, Rabia; Rasul, Sadia (Asian Journal of Chemistry, 2015)
Adsorptive eradication of cadmium(II) from water was studied in batch mode using novel synthesized polyaniline/Madhuca longifolia and polyaniline/Eugenia jambolana composites. The optimum conditions of sorption of cadmium(II) solution with polyaniline/Madhuca longifolia composite were: 0.6 g/50 mL adsorbent dose, 40 min contact time, 5 pH and 50 °C temperature. Whereas for polyaniline/Eugenia jambolana composites, these conditions were:adsorbent dose 0.6 g/50 mL, 80 min contact time, 6 pH and 30 °C temperature. Langmuir isotherm model was applicable in both cases, indicating that monolayer chemisorptive removal of metal ions occurred more on homogeneously distributed binding sites of composites as compared to physiosorption on multilayers binding sites. The maximum adsorption capacity of polyaniline/Madhuca longifolia composite was found to be 0.498 mg/g, while in case of polyaniline/Eugenia jambolana was 0.444 mg/g. The feasibility and spontaneity of this process was shown by negative value of DG°. Freundlich constant KF values were: 8.89 × 10-5 and 4.47 × 10-5 mgL-1/n L1/n g-1 for polyaniline/Madhuca longifolia and polyaniline/Eugenia jambolana respectively. Results show that polyaniline/Madhuca longifolia is better adsorbent for cadmium(II) removal and shows more adsorption than polyaniline/Eugenia jambolana. Polyaniline/Madhuca longifolia and polyaniline/Eugenia jambolana were characterized by UV/visible spectroscopy, FT-IR spectroscopy and Boehm's titration.